TEACHERS’ PERCEPTION OF PROFESSIONALISM IN COMPETENCY-BASED MEDICAL EDUCATION: ARE THERE ANY DIFFERENCES? - Rachmad Sarwo Bekti; Carissa Putri Irnanda; Setyawati Soeharto (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2018)
Background: Medical professionalism learning for medical students in Faculty of Medicine of Universitas Brawijaya (FMUB) requires some clear indicators or values because of the Competency-based Curriculum (KBK). Those values can be arranged by looking for the local wisdom which is a group of visions or values from the lecturers’ perceptions toward professionalism. This research was aimed to reveal the specific components of professionalism in FKUB perceived by faculty. Method: This research was designed as a qualitative research by using semi-structured interviews of targeted subjects to gather the data constructs. The questions in interviews were designated to dig out the informer’s perception in interpreting medical professionalism, based on their experiences, current visions, and hopes. Standardized qualitative analysis were applied to reveal the main themes of the responses. Results: Themes which came up as the components of professionalism from 15 lecturers’s perceptions were categorized as follow: attitude, clinical competence, and knowledge. Those main components were mentioned in National and International Standards related to professionalism, but not all the sub-components were mentioned. Spirituality and medical attire which became the sub-component of attitude were considered as specific construct of professionalism perceived by FKUB lecturers. Conclusion: The concept of professionalism rooted on spirituality and expressed into proper attire in this research was expected to become a local wisdom of medical professionalism in Indonesia. It is advised that the results of this study can help the medical program administrator to develop instruments that nurture the professionalism development of students. Further research might be conducted by using different university context or by taking samples from larger faculty perspective with different specialization.